IMPLEMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN MELALUI PROGRAM SEKOLAH BEBAS SAMPAH DI SDN 1 BARENG KABAT BANYUWANGI - Imam Mashuri; Nur Karimah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
This study aims to describe the education of environmental-care characters through the School Garbage-Free Program at SDN 1 Bareng District of Kabat consisting of planning, implementing, and evaluating. The type of research used is descriptive qualitative. The subjects of the study were elementary school SDN 1 Bareng. Techniques Data collection uses observation, interviews and documentation. Data analysis is done by data collection, data reduction, data presentation, and conclusion. Testing the validity of data using, persistence, triangulation technique, source triangulation and member check. Based on the result of the research, it can be concluded that: (1) Planning phase of School Garbage free program includes preparation of work program of Sekolah Bebas Sampah, scheduling activity schedule, and budget funding and activity fund source. (2) The implementation of the School Garbage free program uses a strategy of habituation through conditioning, routine, programmed, spontaneous and exemplary. Implemented programs include socialization of the importance of maintaining cleanliness, daily and monthly cleanliness, provision of hygiene facilities, separating organic and inorganic waste, and utilizing waste into more useful items. (3) Evaluation of School Free Program for the students of SDN 1 Bareng Kabat elementary school that is integrated in attitude assessment in each student progress report card. The conclusion is that the education of the environment-care character of the School Free Garbage program through the stages of planning, implementation, and Assessment.